Speed Runner S.A. - Tateishi, Víctor (Universidad ESAN. ESAN Ediciones, 2001)
The case presents a production company that intends to maintain its distribution and sales policies in a context of recession. In this sense, it is presented for discussion and exchange of ideas. In the middle of the discussion, it would be interesting to be able to differentiate what is a policy decision from what is the real market situation.

El caso presenta a una empresa productora que pretende mantener sus políticas de distribución y ventas en un contexto de recesión. En este sentido se presenta para el debate y el intercambio de ideas. En medio de la discusión, sería interesante poder diferenciar lo que es una decisión de política de lo que es la situación real del mercado.
Keywords: Motor vehicles; Vehículos automotores; https://purl.org/pe-repo/ocde/ford#5.02.04